Економічна ефективність застосування IoT - Денькович, О. М. (ХНУРЕ, 2024)
The application of Internet of Things (IoT) technology has garnered significant attention in various sectors due to its potential to enhance efficiency and productivity. This paper examines the economic effectiveness of implementing IoT solutions in different industries. By leveraging IoT devices to collect and analyze real-time data, organizations can optimize resource allocation, improve operational processes, and reduce costs. The benefits of IoT adoption extend beyond cost savings, encompassing enhanced decision-making capabilities and new revenue streams through data monetization. However, challenges such as security concerns, interoperability issues, and initial investment costs need to be addressed to realize the full economic potential of IoT deployment. This presentation will explore case studies and empirical evidence to illustrate the economic impact of IoT across diverse sectors and provide insights into maximizing its benefits while mitigating associated risks.
Keywords: ефективність застосування IoT; Internet of Things (IoT) technology